THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK PRICES MODERATED BY INSTITUTIONAL OWNERSHIP - Vinta Desi, Anistya; Mulyanah (Management Science Research Journal, 2024)
This study was conducted to examine the effect of financial performance on stock prices with institutional ownership as a moderating variable. The final sample studied using purposive sampling technique in this study amounted to 65 data points during the observation period from 2019–2023, with healthcare companies as the research population. A quantitative method was chosen for this study, with data obtained from the Indonesia Stock Exchange and the official websites of the sample companies. In this study, multiple linear regression analysis was used to predict the influence of financial performance, stock prices, and institutional ownership, while Moderated Regression Analysis (MRA) was used to test the moderating variable. The results of the tests show that financial performance measured by Earnings Per Share (EPS) has a positive effect on stock prices. Financial performance measured by Return on Assets (ROA) also affects stock prices. Institutional ownership does not moderate the effect of EPS on stock prices, but institutional ownership can moderate the effect of Return on Assets (ROA) on stock prices.